Xanthotoxin affects depression-related behavior and neurotransmitters content in a sex-dependent manner in mice - Kowalczyk, J.; Nakos-Bimpos, M.; Polissidis, A.; Dalla, C; Kokras, N; Skalicka-Wozniak, K.; Budzynska, B. (Behav Brain Res, 2021)
The present study aimed to evaluate xanthotoxin's influence on male and female Swiss mice's depression-like behaviors and investigate the potential mechanism of this effect. Naturally derived furanocoumarin (the Apiaceae family), xanthotoxin, administered acutely (12.5 mg/kg), diminished the immobility level in the forced swim test only in males. The immobility level was lower in females than males, which may be associated with a higher serotonin level in the female prefrontal cortex. A dose-dependent increase of serotonin and noradrenaline was reported in the reverse-phase ion-pair liquid chromatography in the female prefrontal cortex but not in the hippocampus. We suggest that xanthotoxin may exert antidepressant properties and affect males and females differently. The increasing level of serotonin in the male and female prefrontal cortex may underlie this effect.
Keywords: Animals; Antidepressive Agents/administration & dosage/*pharmacology; Behavior, Animal/*drug effects; Coumarins; Depression/*drug therapy; Female; Forced swimming test; Hippocampus/*drug effects/metabolism; Male; Methoxsalen/administration & dosage/*pharmacology; Mice; Noradrenaline; Norepinephrine/*metabolism; Plant Preparations; Prefrontal Cortex/*drug effects/metabolism; Serotonin; Serotonin/*metabolism; Sex Characteristics; Sex Factors